Preparation of alkali-activated oil shale residue-slag geopolymer-based binder using calcium carbide slag and sodium carbonate as alkali activator - Chenchen Luo; Bo Zheng; Yi Li; Qiao Yang (PLoS ONE, 2025)
Based on the reuse of industrial solid wastes such as calcium carbide slag, slag, and oil shale residue, this work utilizes oil shale residue and slag as precursor materials, calcium carbide slag and sodium carbonate as alkaline activator to prepare a geopolymer-based binder. Mix proportion experiments of the geopolymer-based binder with varying oil shale residue contents were designed. Chemical composition and microstructure of the alkaline-activated oil shale residue-slag geopolymer-based binder system were analyzed using X-ray Fluorescence Spectrometer (XRF), X-ray Powder Diffractometer (XRD), and Scanning Electron Microscope (SEM). Meanwhile, the fluidity and mechanical properties of the material were also investigated. The results indicate that as the oil shale residue content increases, the fluidity and 3-day compressive strength and splitting tensile strength of the filling slurry gradually decrease, while the 28-day strength first rises and then falls, reaching a maximum when the oil shale residue content is 20%. When the oil shale residue content is below 20%, the hydration product content gradually increases, and the microstructure tends to be denser. However, as the oil shale residue content further increases, the hydration product gradually decreases, and the microstructure becomes poorer. Therefore, the optimal oil shale residue content is 20%. The geopolymer-based binder system prepared in this paper is a low-carbon, environmentally friendly, and high-performance material system, its research and development are of great significance to the human society.